Phosphorylated neurofilament heavy subunit (pNF-H) in peripheral blood and CSF as a potential prognostic biomarker in amyotrophic lateral sclerosis. Issue 4 (31st October 2012) - Boylan, Kevin B; Glass, Jonathan D; Crook, Julia E; Yang, Cui; Thomas, Colleen S; Desaro, Pamela; Johnston, Amelia; Overstreet, Karen; Kelly, Crystal; Polak, Meraida; Shaw, Gerry
Abstract : Background: The phosphorylated neurofilament heavy subunit (pNF-H), a major structural component of motor axons, is a promising putative biomarker in amyotrophic lateral sclerosis (ALS) but has been studied mainly in CSF. We examined pNF-H concentrations in plasma, serum and CSF as a potential biomarker for disease progression and survival in ALS. Methodology: We measured pNF-H concentration by monoclonal sandwich ELISA in plasma (n=43), serum and CSF (n=20) in ALS patients collected at the Mayo Clinic Florida and Emory University. We included plasma from an ALS cohort (n=20) from an earlier pilot study in order to evaluate baseline pNF-H levels in relation to disease progression using the Amyotrophic Lateral Sclerosis Functional Rating Scale (ALSFRS-R), survival and anatomical region of ALS onset. Results: Higher pNF-H levels in plasma, serum and CSF showed evidence of association with faster decline in ALSFRS-R. There was evidence for a relationship of higher serum and plasma pNF-H levels with shorter survival, although evidence was weaker for CSF. pNF-H concentration in plasma (n=62) may be higher in patients with bulbar onset than in patients with spinal onset. Conclusions: In ALS, increased pNF-H concentration in plasma, serum and CSF appears to be associated with faster disease progression. Factors affecting pNF-H levels or their detection in serum and plasma in relation to disease course may differ from those in CSF. Data raising the possibility that site of ALS onset (bulbar vs spinal) may influence pNF-H levels in peripheral blood seems noteworthy but requires confirmation. These data support further study of pNF-H in CSF, serum and plasma as a potential ALS biomarker.